An Evaluation of Changeability of Parameters Describing Abbot Curve during a Wavelet Decomposition Process - Zajac, Jozef; Makieła, Włodzimierz; Stępień, Krzysztof; Gogolewski, Damian (Manufacturing Technology Journal, 2014)
Results of signals analysis was done using wavelet transform, which have different curves of wavelets and depend on the basic wavelet, which were applied. Thus, it is sometimes not possible to conduct a wavelet transform of a given profile with the use of any basic wavelets and to obtain results that are similar to the measured signal. The aim of this was work was an optimization of a basic wavelet selection used for an analysis of surface roughness. In the work an analysis of Abbot-Firestone curve parameters was performed on subsequent decomposition levels and for various basic wavelets.
Keywords: wavelet transform; Abbot-Firestone curve; decomposition